INTEGRATING CROSS-CURRICULAR TEACHIING AND CALL IS FEASIBLE: AN INTERVENTION PROJECT IN PRIMARY EDUCATION - Rascón Moreno, Diego (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Foreign language teaching offers an invaluable opportunity to bring peace, health, environmental, gender, sex, moral and civic, road safety, and consumer education into the classroom. Addressing these topics in all subjects throughout the compulsory educational period was actively encouraged in Spain from 1991 to 2007 Unfortunately, many members of the teaching profession believe that this way of dealing with them did not succeed. This idea is partly confirmed by the information I gathered in 2006 and 2007 from the majority of schools in the city of Jaén as part of my doctoral research. It can be concluded from the data collected that most teachers of English in these schools rely exclusively on published materials to deal with cross-curricular topics of moral nature and that many of these resources do not cover this content sufficiently. Thus, to make up for this shortcoming, teachers should create material on these issues, which is relatively uncomplicated thanks to Information and Communication Technology (ICT). This is what I advocate here, that teachers of English resort to designing ICT activities to compensate for these essential issues being poorly addressed by publishers. This paper describes a project carried out in a primary English classroom that proves that introducing cross-curricular content in their lessons is something that foreign language teachers can easily do now through computer technology. Resumen La enseñanza de lenguas extranjeras ofrece una inmejorable oportunidad para integrar en el aula la educación para la paz, la salud, el medio ambiente, la igualdad entre los sexos, la educación sexual, la educación moral y cívica, la educación vial y la educación del consumidor. El tratamiento de estos temas en todas las asignaturas a lo largo de la etapa escolar obligatoria se fomentó en España entre los años 1991 y 2007. Desgraciadamente, existe la sensación entre muchos miembros de la comunidad educativa de que esta manera de abarcarlos no fue exitosa. La información que recogí en 2006 y 2007 en la mayoría de los colegios e institutos de la ciudad de Jaén como parte de mi investigación doctoral confirma parcialmente esta idea. Se puede concluir de los datos obtenidos que gran parte del profesorado de inglés de los centros visitados confía exclusivamente en los materiales editados a la hora de tratar los Temas Transversales y que muchos de estos recursos no cubren el contenido suficientemente. Así pues, con el objeto de compensar esta deficiencia, los profesores deberían crear material sobre estos temas, lo que es relativamente sencillo gracias a las Tecnologías de la Información y la Comunicación. Esto es por lo que se aboga aquí, por que los profesores de inglés recurran al diseño de actividades en formato electrónico para suplir el escaso tratamiento que muchas editoriales dan a estos imprescindibles temas. En este artículo describo un proyecto llevado a cabo en un aula de Inglés de Primaria que demuestra que la introducción de contenido transversal es algo que los profesores de lenguas extranjeras pueden fácilmente hacer ahora a través de la informática.